2010
DOI: 10.1179/joc.2010.22.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Ceftriaxone-Induced Pancreatitis in a Pediatric Patient: Case Report

Abstract: We describe the first case of probable ceftriaxone-induced pancreatitis in a 2-year-old child. The patient was admitted to Santobono-pausilipon Children's Hospital with fever, vomiting and diarrhea and was treated with ceftriaxone 700 mg/day by intramuscular route. After the second administration of ceftriaxone, laboratory data revealed an increase in amylase. The patient's abdomen was mildly distended and diffusely painful. Drug-induced pancreatitis was considered and ceftriaxone was immediately discontinued,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…22 Interestingly, several cephalosporins, including cefuroxime, cefotaxime and cefixime, showed a possible or probable causal relationship in our causality assessment of individual cases. To this day, ceftriaxone has been the only antibiotic of this class to be reported associated with AP, [23][24][25][26][27][28] possibly via formation of gallstones. 24 As cases of biliary AP were excluded from our study, it seems that this pathomechanism of ceftriaxone-induced AP may not apply to all other cephalosporins.…”
Section: Discussionmentioning
confidence: 99%
“…22 Interestingly, several cephalosporins, including cefuroxime, cefotaxime and cefixime, showed a possible or probable causal relationship in our causality assessment of individual cases. To this day, ceftriaxone has been the only antibiotic of this class to be reported associated with AP, [23][24][25][26][27][28] possibly via formation of gallstones. 24 As cases of biliary AP were excluded from our study, it seems that this pathomechanism of ceftriaxone-induced AP may not apply to all other cephalosporins.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of domperidone, a follow-up study showed that its use in dysphagic pediatric patients affected by brain injury could be optimized, and the risk of vomiting minimized by assessing the presence/absence of pyloric obstructions via a gastric transit examination early after initiating domperidone administration [33]. The most frequently reported therapeutic main group of drugs in previous European studies were antibiotics [18,34,35]. We instead found that vaccines (hexavalent, anti-pneumococcal, anti-meningococcus, trivalent measles/mumps/rubella) were those most commonly reported, in line with another observational survey [18,[36][37][38].…”
Section: Number Of Adrsmentioning
confidence: 99%
“…In approximately 60% of these cases, the carriers of biliary lithiasis are asymptomatic, but when symptoms or clinical signs are manifested, nearly 70% of the patients will undergo surgical procedures due to acute or chronic cholecystitis 15 . When biliary microlithiasis (stones up to 3 mm) is present, typically involving multiple calculi, and approximately 20% of patients develop pancreatitis, as the microlithiasis may migrate to the common bile duct and pass through the papilla causing relevant injuries associated with an acute inflammatory process 16,17 . It must be emphasized that ceftriaxone has a broad spectrum of action with a long half-life.…”
Section: ■ Discussionmentioning
confidence: 99%